2019
DOI: 10.7573/dic.212584
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of mepolizumab in severe refractory eosinophilic asthma: results in clinical practice

Abstract: Background Asthma is an inflammatory disease of the airways with symptoms that vary over time and intensity, sometimes leading to disability or even death. Eosinophilic asthma accounts for 25% of cases of severe asthma. It is mediated by eosinophils regulated by interleukin-5 (IL-5), the target of mepolizumab, which has been recently licensed as an add-on treatment of severe refractory eosinophilic asthma. The aim of this study was to evaluate the effectiveness and safety of mepolizumab in clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
19
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 10 publications
11
19
0
3
Order By: Relevance
“…15,16 Recently, several smaller studies based on real-world data have also shown that mepolizumab is associated with a reduction in exacerbations. 17,18 Taken together with our findings, this highlights the beneficial effect of mepolizumab on exacerbation frequency irrespective of seasonality.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…15,16 Recently, several smaller studies based on real-world data have also shown that mepolizumab is associated with a reduction in exacerbations. 17,18 Taken together with our findings, this highlights the beneficial effect of mepolizumab on exacerbation frequency irrespective of seasonality.…”
Section: Discussionsupporting
confidence: 85%
“…Although not a formal objective of this study, we observed reductions in chronic OCS use with mepolizumab treatment, a finding that is consistent with results from the previous clinical trials of mepolizumab, 12,19,20 as well as other recent analyses of real-world data on mepolizumab treatment. 17,18 A recent longitudinal database study showed that increasing the number of OCS prescriptions is associated with increased odds of experiencing an adverse event. Thus, a reduction in the use of OCS may improve outcomes in patients with asthma.…”
Section: Discussionmentioning
confidence: 99%
“…The results show a clear improvement for the patients, which is reflected in a reduction of the number of exacerbations, improved clinical control, and a reduction in the use of OCS. The data are very similar to those in the literature, both in the controlled clinical trials (5-9) and in the real-life studies carried out with the drug (11,(15)(16)(17)(18). In this way, the type of patients included in our series are very similar to those already published, both in existence of associated comorbidities and in the presence of secondary effects attributed to the administration of the drug.…”
Section: Discussionsupporting
confidence: 87%
“…Eosinophilia during asthma development is associated with pro-inflammatory cytokines such as IL-4, IL-5 and IL-13 [23,24]. These cytokines are involved in driving the maturation, activation, and accumulation of eosinophils within damaged lung lesions, leading to IgE production, airway inflammation, mucus overproduction, and AHR [25,26]. Therefore, the modulation of pro-inflammatory cytokines is regarded as an important strategy for controlling asthma.…”
Section: Discussionmentioning
confidence: 99%